Teungku Inong and Digital Da'wah in Aceh: Balancing Social Media, Career, and Family through an Islamic Communication Perspective - Sari, Fitri Meliya; Sikumbang, Ahmad Tamrin; Rubino, Rubino (El-Usrah: Jurnal Hukum Keluarga, 2025)
The rise of social media has created new opportunities for female preachers in Aceh, known as Teungku Inong (female clerics), to disseminate religious teachings in broader, more inclusive, and interactive ways. This development marks a significant shift in women's roles within digital da'wah (Islamic preaching), while simultaneously presenting new challenges particularly in balancing their public responsibilities as religious leaders with their private roles within the family. This study examines the impact of social media engagement on the family life of Teungku Inong, focusing on the dynamics of their dual roles and the strategies employed to navigate the demands of both professional and domestic spheres. Utilizing a qualitative case study approach, the research centers on female clerics in North Aceh and draws on theories of social roles and Islamic communication. Data were collected through in-depth interviews and content analysis of their social media presence. The findings reveal that the ability of Teungku Inong to manage dual responsibilities is strongly supported by both emotional and technical assistance from family members, particularly husbands and siblings. Key strategies include disciplined time management, open family communication, and the adaptive use of digital tools to facilitate da'wah activities without compromising domestic obligations. Sociologically, this study highlights the essential role of family support and digital literacy in enabling female preachers to thrive in the digital era. From the perspective of Islamic communication, the emergence of female clerics utilizing social media as a medium for da'wah represents a progressive development in both the professionalization of da'wah and the evolving roles of women in Islamic discourse. These findings contribute to a deeper understanding of women's participation in digital religious spaces and the negotiation of work–family balance in socio-religious contexts